Critical roles of hMAGEA2 in induced pluripotent stem cell pluripotency, proliferation, and differentiation. (11th September 2017) - Park, Song; Sung, Yonghun; Jeong, Jain; Choi, Minjee; Lee, Jinhee; Kwon, Wookbong; Jang, Soyoung; Park, Si Jun; Kim, Jae Young; Kim, Sung Hyun; Yoon, Duhak; Ryoo, Zae Young; et al.
Abstract : Induced pluripotent stem (iPS) cells are important for clinical application and stem cell research. Although human melanoma‐associated antigen A2 (hMAGEA2) expression is known to affect differentiation in embryonic stem cells, its specific role in iPS cells remains unclear. To evaluate the function of hMAGEA2 and its characteristics in iPS cells, we produced hMAGEA2‐overexpressing iPS cells from hMAGEA2‐overexpressing transgenic mice. Although the iPS cells with overexpressed hMAGEA2 did not differ in morphology, their pluripotency, and self‐renewal related genes (Nanog, Oct3/4, Sox2, and Stat3), expression level was significantly upregulated. Moreover, hMAGEA2 contributed to the promotion of cell cycle progression, thereby accelerating cell proliferation. Through embryoid body formation in vitro and teratoma formation in vivo, we demonstrated that hMAGEA2 critically decreases the differentiation ability of iPS cells. These data indicate that hMAGEA2 intensifies the self‐renewal, pluripotency, and degree of proliferation of iPS cells, while significantly repressing their differentiation efficiency. Therefore, our findings prove that hMAGEA2 plays key roles in iPS cells.